2014
DOI: 10.1128/aem.02972-13
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Dynamics of Toxic Microcystis spp. and Microcystin-Degrading Bacteria in Dianchi Lake, China

Abstract: bToxic cyanobacterial blooms directly threaten both human safety and the ecosystem of surface waters. The widespread occurrence of these organisms, coupled with the tumor-promoting properties of the microcystin toxins that they produce, demands action to mitigate their potential impacts and, thus, a robust understanding of their ecological dynamics. In the present work, the abundance of toxic Microcystis spp. and microcystin (MC)-degrading bacteria in Dianchi Lake, located in Yunnan Province, China, was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…Similar results were observed by Zhu et al (2014) [49], who found that seasonal variations of extracellular MCs in water were related to variations in MCs-degrading bacterial abundance based on mlr A gene analysis. Our results, together with other studies, suggest that these mlr A + bacteria make an important contribution to the biodegradation of MCs in water [49,50]. However, the real contribution of the total biodegradation of MCs in nature can only be understood by considering the whole MCs-degrading bacterial community which, according to our results, goes beyond the analysis of the mlr A gene.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were observed by Zhu et al (2014) [49], who found that seasonal variations of extracellular MCs in water were related to variations in MCs-degrading bacterial abundance based on mlr A gene analysis. Our results, together with other studies, suggest that these mlr A + bacteria make an important contribution to the biodegradation of MCs in water [49,50]. However, the real contribution of the total biodegradation of MCs in nature can only be understood by considering the whole MCs-degrading bacterial community which, according to our results, goes beyond the analysis of the mlr A gene.…”
Section: Discussionsupporting
confidence: 89%
“…3a). This result was consistent with Zhu et al (2014), who also revealed that the mlrA gene copy number exhibited peak in the months following observed peaks of MCs concentration and water temperature in Dianchi Lake, China. The phenomenon here implied that MCLR in water column where biofilms submerged can act as nutrient sources for growth of MC-degrader population in biofilms.…”
Section: Seasonal Variation In Mc-degrader Abundance Within Biofilms supporting
confidence: 94%
“…; Zhu et al. ). Sphingomonadales species are well adapted to the cyanobacterial phycosphere, especially that of Microcystis with regard to their capacity to degrade cyanobacterial toxins and other problematic organic compounds (Wilkes et al.…”
Section: Resultsmentioning
confidence: 98%